A Review on Ethnomedicinal Claims of Desmodium Triquetrum (L.) DC. - Manave, Ankita A; Patel, Bhupesh; Pandya, Preeti (International Research Journal of Ayurveda & Yoga, 2022)
Desmodium triquetrum (L.) DC.is synonym of Tadahagi triquetrum (L.) H.Ohashi belongs to the family Fabaceae. Desmodium triquetrum (L.) DC. is traditionally used in common cold, sore throat, hemoptysis due to lung diseases, hepatomegaly, enteritis, traumatic injury, etc. Aim: The aim of this review is to provide comprehensive information on ethnomedicinal claims of Desmodium triquetrum (L.) DC. from published literatures, books related to ethnobotany and ethnomedicine. Materials and Methods: All the available information on Desmodium triquetrum (L.) DC.was collected via published literatures, books like Medicinal plants of Gujarat, Reviews on Indian medicinal plants, The wealth of India NISCAIR, etc. The obtained information was distributed into part-wise ethnomedicinal claims, region-wise traditional claims, local names in different languages, and therapeutic indications.Result: It has been found to be reported in more than 23 states in India, widely distributed in western parts of India common in Maharashtra, Kerala, Karnataka, Gujarat etc.Its root, leaves, and the whole plant has been recommended in 19 different diseases both externally and internally. The whole plant has maximum application in 12 different diseased conditions, followed by root and leaves in 4 and 3 diseases respectively. Conclusion: Desmodium triquetrum (L.) DC. is widely used for treatment of chronic cough and tuberculosis and also, the leaves have been used as a substitute for tea by hill tribes in upper Assam. As the findings, Desmodium triquetrum (L.) DC. need to explore with the help of detailed investigation, especially through pharmacological properties.